Experimental study on compressive strength of permeable concrete with shredded plastic fiber and plastic pellets. (2022) - Vijayakumar, M.; Anusha, G.; Athipathy, M.; Krishnakumar, P.
Abstract: Water logging on highways and parking lots is a big concern in many projects, especially during the monsoon, because pavements and floors are generally impervious. This necessitates a significant investment in maintenance and storm water drainage systems, which may become clogged at peak overflow. Aside from that, there are a slew of other issues that occur as a result of the preceding. In such cases, it is critical to consider a cost-effective solution that aids in the resolution of all of the aforementioned issues. Permeable concrete is the best answer to the problem mentioned above. This paper outlines the many studies that have been conducted in order to meet the demand for permeable concrete by using plastic pellets and shredded plastics as additional materials in the production of permeable concrete.